Apparent digestibility coefficients of processed agro‐food by‐products in European seabass (Dicentrarchus labrax) juveniles. (24th January 2018) - Campos, I.; Matos, E.; Aragão, C.; Pintado, M.; Valente, L.M.P.
Abstract: Apparent digestibility coefficients (ADCs) of processed agro‐food by‐products were assessed in European seabass ( Dicentrarchus labrax ). Each experimental diet was obtained by replacing 300 g/kg of a commercial‐based diet used as reference (REF) with a test ingredient: wheat germ (GERM), okara meal (OKA), poultry by‐product meal (POULT), steam hydrolysed (FeHY) and enzyme‐treated feather meal (FeENZ), beta‐lactoglobulin (β‐Lg) and peptide fractions >3, 000 Da obtained from brewer's yeast (YeastP) and fish by‐products (FishP). Dry matter ADC was highest in β‐Lg (95%) and lowest in OKA (40%). Protein ADCs were high in β‐Lg, FishP, GERM and POULT (>93%); intermediate in FeHY and FeENZ (85%–88%); and moderate in OKA and YeastP (70%–78%). The essential amino acids' ADC mean was above 91% in POULT, β‐Lg, GERM and FishP, 84%–89% in FeHY and FeENZ and 73%–76% in YeastP and OKA. Energy ADC was highest in POULT and β‐Lg (89%–95%) and lowest in YeastP and OKA (61%–64%). Lipid ADC was highest for POULT and GERM (100%). Phosphorus ADC was lowest in GERM (19%) and highest in β‐Lg (88%). FeHY, FeENZ, POULT, GERM, FishP and β‐Lg are highlighted as protein sources for European seabass.